Desain Dan Analisis Kualitas Pencahayaan Berbasis Perangkat Lunak Dialux Evo 8.1 - Riski Febriyursandi; Azriyenni Azhari Zakri; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This research develops and implements a method for calculating lighting systems for classrooms at Khairul Ummah Islamic Boarding School. The lumen method is one of the methods used to determine the number of luminaires needed to improve lighting quality according to the SNI 6197: 2011 standard. The number of luminaires obtained in this study was included in the simulation for DIALux evo 8.1 software. The results obtained from this study show that the lighting in the classrooms at MTs and MA Khairul Ummah Islamic Boarding School has not reached the recommended standard for classrooms, where the direct measurement results of the average lighting level of class IX-E is 10.79 lux, while in the class X IPA 3 is 11.66 lux. To improve this condition, class IX-E requires the number of luminaires of 15 points and class X IPA 3 requires a luminaire of 12 points. The difference in results obtained from mathematical calculations using the lumen method and the simulation results of DIALux software for class IX-E is 15.6% and in class X IPA 3 is 3.4%. The value of investment costs is necessary in order to make improvements to the lighting system in these two schools which are worth Rp. 2,700,000.00 to provide 27 Philips LED bulb 27 watt lamps.Keywords: Classroom, DIALux evo 8.1, Investmen Cost, Lighting, Lumen Method